[tex]\displaystyle\bf\\X(t)=\frac{1}{6} t^{3} -6t^{2} -2t+13\\\\\\V(t)=X'(t)=\frac{1}{6} \cdot(t^{3} )'-6\cdot(t^{2} )'-2\cdot t'+13'=\frac{1}{6} \cdot 3t^{2} -6\cdot 2t-2\cdot 1+0=\\\\=0,5t^{2} -12t-2\\\\t=2\\\\V(2)=0,5\cdot 2^{2} -12\cdot 2-2=2-24-2=-24[/tex]
Наверно перед 6t² знак плюс , а не минус ?
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\X(t)=\frac{1}{6} t^{3} -6t^{2} -2t+13\\\\\\V(t)=X'(t)=\frac{1}{6} \cdot(t^{3} )'-6\cdot(t^{2} )'-2\cdot t'+13'=\frac{1}{6} \cdot 3t^{2} -6\cdot 2t-2\cdot 1+0=\\\\=0,5t^{2} -12t-2\\\\t=2\\\\V(2)=0,5\cdot 2^{2} -12\cdot 2-2=2-24-2=-24[/tex]
Наверно перед 6t² знак плюс , а не минус ?